(3QSGdI aj PcQ CSHGH GdQYO hGdHQbs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3fbhd Ef GdCQYGO hJchf ef CSHGH SHYI s
(3BNQgG (B:s
(3hYdi gPg GdLedI JJhdO GdUhGYb hgPG eG GQOfG Cf fHjf hef Gddg GdJhajb hGdgOGjI hGdJMbjb s
(3eUhQI Yf GdeJMa GdHQjWGfi Qbe (B16659 ADDs
(3jdjgG QSGdI ddeDda ai eYfi bhd GdUhajI (B" (3ef YQa SQ GdbOQ abO GdMO (B" (3ai UaMI hfUas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B54 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs